Decision Making Process through Technical Analysis in New York Stock Exchange (NYSE) Stock Trading (Case Study: Shares of Companies Supporting the Genocide War in Palestine for the Period November 2022 – November 2023) - Asmara, Rizqy Winny (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to carry out technical analysis for the decision-making process in stock price movements listed on the New York Stock Exchange (NYSE). With a focus on company shares linked to support for the genocidal conflict in Palestine. The role of finance in the context of this conflict has been the subject of widespread debate and controversy. Therefore, technical analysis is considered a tool that can provide an objective view of market behavior, while still considering the social and humanitarian impact of companies involved in support of genocide. This research uses four technical analysis tools including Moving Average Coverage Divergence (MACD), Stochastic, Relative Strength Index (RSI) and Bollinger Bands, this aims to see the level of effectiveness of each of these tools in reading stock movements.